Model-based control strategy to reduce the fault current of a synchronous generator under short-circuit - Greidanus, Mateo Daniel Roig (2020)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Engenharia Elétrica, Florianópolis, 2020.